Object-oriented Analysis and Design of an ECG Storage and Retrieval System Integrated with an HIS - Wang, C.; Ohe, K.; Sakurai, T.; Nagase, T.; Kaihara, S. (Methods of Information in Medicine, 1996)
For a hospital information system, object-oriented methodology plays an increasingly important role, especially for the management of digitized data, e.g., the electrocardiogram, electroencephalogram, electromyogram, spirogram, X-ray, CT and histopathological images, which are not yet computerized in most hospitals. As a first step in an object-oriented approach to hospital information management and storing medical data in an object-oriented database, we connected electrocardiographs to a hospital network and established the integration of ECG storage and retrieval systems with a hospital information system. In this paper, the object-oriented analysis and design of the ECG storage and retrieval systems is reported.
Keywords: Object-oriented Systems; Integration; ECG; HIS